Investigation of epimer formation in amide coupling reactions: an experiment for advanced undergraduate students - Fray, Michael J. (American Chemical Society, Division of Chemical Education, 2014)
An experiment is described to investigate how the choice of coupling agent and reaction conditions affects the ratio of epimers formed in the sensitive amide-coupling reaction between N-Boc or N-benzoyl (R)-phenylglycine and (S)-valine methyl ester. The experiment, which is suitable for third-year undergraduates, is designed to teach about important synthetic methods and reaction mechanisms, and to develop skills in designing experiments, data analysis, and team work.